Makna Dari Bentuk-Bentuk Fi’il Mazid Dalam Surat Maryam Dan Surat Al-Anbiyaa’ (Kajian Analisis Morfologi) - Nurul Salis Alamin; Raisa Anisah (Journal on Education, 2024)
In this research, the researcher analyze about Fi’il mazid (verb with affix) which is found in Surah Maryam and Al-Anbiyaa’, because in the both Surah the researcher found some Fi’il mazid which is only found in another Surah in Al-Qur’an. The purpose of this study is to give the definition about Fi’il mazid that has been found in Surah Maryam and Al-Anbiyaa and analyze the meaning of every affix found in the verb. This research is a library research . The researcher used documentary research, and for analyzing the data the researcher used morphology analysis method. The result of this analysis shown that: the form of Fi’il mazid that has been found in Surah Maryam and Al-Anbiyaa is the comon Fi’il mazid that can be found in Arabic language. There are 41 Fi’il mazid found in Surah Maryam and 48 Fi’il mazid found in Surah Al-Anbiya, and the meaning of the affixes of the verb fopound in the both Surah is the common meaning that usually used and found in Arabic.